METHOD AND SYSTEM OF PRODUCT DEVELOPMENT PROCESS FOR CHEMICAL COMPOSITIONS USING HIGH VOLUME MODELING - BALK, THOMAS, J; WOLLENBERG, ROBERT, H (2006)
A method and system of transforming a product development process to reduce time in bringing a product to market through high throughput experimentation and advanced statistics and informatics, to transform the product development to a level of higher correlation with engine tests, and to develop better commercial products. This is achieved by modeling in Silico a plurality of component molecular models; deriving in Silico molecular characteristics (descriptors) for each of the plurality of compiled molecular models; creating at least one combinatorial library database record for each of the formulations, the at least one record having a plurality fields for storing information about compositional characteristics; receiving specification requirements for a lubricating oil composition; selecting from a database entries corresponding to compositions having specifications comparable to the received specification requirements; formulating a new lubricating oil composition to comply with received specification requirements; testing the new lubricant oil for compliance with received specification requirements; repeating the selecting, formulating, and testing steps until compliance with received specification requirements is achieved; and correlating the new lubricating oil composition to actual engine performance. L'invention concerne un procédé et un système pour transformer un processus de développement de produits, permettant de réduire le temps de mise sur le marché d'un produit grâce à une expérimentation grande capacité et des statistiques ainsi que des produits informatiques améliorés, ceci permettant de transformer le développement du produit à un niveau de corrélation élevé, au moyen de tests pratiqués sur des moteurs, et de développer de meilleurs produits commerciaux. Cela peut être réalisé par modélisation du silicium dans une pluralité de modèles moléculaires de composants ; dérivation des caractéristiques moléculaires du silicium (descripteurs) pour chaque modèle de la pluralité de modèles moléculaires compilés ; création d'au moins un enregistrement de base de données de bibliothèque combinatoire pour chaque formulation ; au moins un enregistrement présentant une pluralité de champs permettant de stocker des informations concernant des caractéristiques de composition ; réception de besoins de spécification pour une composition de lubrifiant ; sélection d'entrées de base de données correspondant à des compositions présentant des spécifications comparables aux demandes de spécifications reçues ; formulation d'une nouvelle composition de lubrifiant conforme aux demandes de spécification reçues ; répétition de la sélection, la formulation, et du test, jusqu'à ce que la conformité aux demandes de spécification reçues soit obtenue ; mise en corrélation de la nouvelle composition de lubrifiant avec les performances réelles du moteur.